Methane Alleviates Acetaminophen-Induced Liver Injury by Inhibiting Inflammation, Oxidative Stress, Endoplasmic Reticulum Stress, and Apoptosis through the Nrf2/HO-1/NQO1 Signaling Pathway. (6th November 2019) - Feng, Yang; Cui, Ruixia; Li, Zeyu; Zhang, Xia; Jia, Yifan; Zhang, Xing; Shi, Jinghong; Qu, Kai; Liu, Chang; Zhang, Jingyao
Abstract : Acetaminophen- (APAP-) induced hepatic injury is an important clinical challenge. Oxidative stress, inflammation, apoptosis, and endoplasmic reticulum stress (ERS) contribute to the pathogenesis. Methane has potential anti-inflammatory, antioxidant, and antiapoptotic properties. This project was aimed at studying the protective effects and relative mechanisms of methane in APAP-induced liver injury. In the in vivo experiment, C57BL/6 mice were treated with APAP (400 mg/kg) to induce hepatic injury followed by methane-rich saline (MRS) 10 ml/kg i.p. after 12 and 24 h. We observed that MRS alleviated the histopathological lesions in the liver, decreased serum aminotransferase levels, reduced the levels of inflammatory cytokines, suppressed the nuclear factor- κ B expression. Further, we found that MRS relieved oxidative stress by regulating the Nrf2/HO-1/NQO1 signaling pathway and their downstream products after APAP challenge. MRS also regulated proteins associated with ERS-induced apoptosis. In the in vitro experiment, the L-02 cell line was treated with APAP (10 mM) to induce hepatic injury. We found that a methane-rich medium decreased the levels of reactive oxygen species (DHE fluorescent staining), inhibited apoptosis (cell flow test), and regulated the Nrf2/HO-1/NQO1 signaling pathway. Our data indicated that MRS prevented APAP-induced hepatic injury via anti-inflammatory, antioxidant, anti-ERS, and antiapoptotic properties involving the Nrf2/HO-1/NQO1 signaling pathway.